TATHBIQ MAHAROH AT TAFKIR DZAT AT TARTIB AL ADNA (LOTS) FI ITQONI AL MUFRODAT AL LUGHOH AL ARABIYAH FI MA’HAD MIRQOTUL ULUM AL ISLAMI - Rodifah, Tatbauhar; Ni’mah, Mamlu’atun; Ulfah, Yeniati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Learning Arabic at the Mirqotul Ulum Islamic boarding school has characteristics that differentiate it from other Islamic boarding schools. This is because this Islamic boarding school pays great attention to mastering Arabic vocabulary, where initially Arabic was something scary and has now turned into something fun because of the learning model. This research aims to determine the Arabic language learning model implemented at the Mirqotul Ulum Islamic boarding school so that they can master one of the skills in Arabic, in the form of listening, speaking, reading, and writing. The objects studied were students and Arabic language teachers. Data analysis in this research uses qualitative descriptive analysis techniques consisting of observation, interview, and documentation stages for data collection. The results of this research show that Arabic language learning at the Mirqotul Ulum Islamic boarding school uses Bloom's Taxonomy in category LOTS (Lower Order Thinking Skills). This application has been integrated in a balanced manner through the abilities possessed by the students of the Mirqotul Ulum Islamic boarding school. In teaching Arabic, we use the method of memorizing vocabulary through trendy songs, both in the 90s and 2000s, so that we can train students to be creative and innovative, as well as create students who can master Arabic vocabulary well and correctly.